Combating antimicrobial resistance with cefiderocol for complicated infections involving the urinary tract. (January 2022) - Wang, Hongmei; Palasik, Brittany N.
Cefiderocol is a unique siderophore cephalosporin antimicrobial agent that has shown promise in treating complicated urinary tract infections (cUTI). Urinary tract infections are commonly diagnosed infections with risk increasing with age and prevalence more common in women. cUTI poses a risk of recurrence and is more likely to be associated with antibiotic-resistant bacteria. The Food and Drug Administration approved cefiderocol for use as a last-line option in the treatment of cUTI including pyelonephritis. Cefiderocol has activity against all forms of carbapenemases due to its ability to overcome the mechanisms of carbapenemase resistance. Because of this, resistance to cefiderocol is unlikely to occur. Studies show cefiderocol is well tolerated among younger patients and patients greater than 65 years of age, the latter making up most of the study population. Renal dose adjustments are recommended. Dose adjustment in the presence of hepatic impairment is not recommended, as hepatic clearance represents a minor elimination pathway for cefiderocol. The ability of cefiderocol to overcome multiple resistance mechanisms makes it a novel choice in combating multidrug-resistant bacteria in the treatment of cUTI.